1998
DOI: 10.1006/viro.1998.9164
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Two Overlapping Papain-like Proteinase Domains Encoded in Gene 1 of the Coronavirus Infectious Bronchitis Virus and Determination of the C-Terminal Cleavage Site of an 87-kDa Protein

Abstract: In a previous report, we showed that proteolytic processing of an 87-kDa mature viral protein from the coronavirus infectious bronchitis virus (IBV) 1a and 1a/1b polyproteins was mediated by two putative overlapping papain-like proteinase domains (PLPDs) encoded within the region from nucleotides 4243 to 5553 of ORF 1a (Liu et al., 1995). In this study, we demonstrate that only the first domain, PLPD-1, is responsible for this cleavage, as deletion of the second domain did not affect the formation of the 87-kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 28 publications
(40 reference statements)
2
65
0
Order By: Relevance
“…We previously demonstrated that PLPD-1 encoded between nucleotides 4243 and 5576 was responsible for the cleavage of the 87-kDa protein at the Gly 673 -Gly 674 dipeptide bond (17), and the catalytic dyad for this activity was the Cys 1274 and His 1437 residues. We then used deletion and mutational analyses to test if either of the two PLPDs is involved in this novel cleavage activity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that PLPD-1 encoded between nucleotides 4243 and 5576 was responsible for the cleavage of the 87-kDa protein at the Gly 673 -Gly 674 dipeptide bond (17), and the catalytic dyad for this activity was the Cys 1274 and His 1437 residues. We then used deletion and mutational analyses to test if either of the two PLPDs is involved in this novel cleavage activity.…”
Section: Resultsmentioning
confidence: 99%
“…A time course experiment was then carried out to further investigate the processing and maturation of the three N-terminal cleavage products (87-, 195-, and 41-kDa proteins). Immunoprecipitation using antiserum V59 (17,21) showed that the 87-kDa protein was detected from IBV-infected cells harvested at 10 h p.i. (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations